Eksplorasi Nilai-Nilai Edukasi Konservasi Mata Air pada Tradisi Ngalun Aik di Lombok Timur - Armin Subhani; Muhammad Shulhan Hadi; Sri Agustina; Lalu Murdi; Haerudin Haerudin (Universitas Hamzanwadi, 2024)
The Ngalun Aik tradition has strong roots and has become an identity in the life of the people of Aik Dewa Village. On the other hand, the spring in Aik Dewa Village not only acts as a source of clean water for daily needs but also plays an important role in local rituals and beliefs related to survival. Therefore, the role of local traditions such as Ngalun Aik is becoming increasingly important to explore and understand in spring conservation efforts. This research uses a qualitative approach to gain an understanding of the educational value of spring conservation in the Ngalun Aik tradition. The respondents in this research involved six male and four female key persons, representing religious leaders, traditional leaders, community leaders, and groups of young men and women. Based on documentation, observation, and interview findings, it can be concluded that the Ngalun Aik tradition in Aik Dewa Village is not only a cultural ritual but also a strong educational platform about the importance of environmental conservation and natural resource management. Through ritual processions, people express their appreciation for water sources as sacred gifts of nature. This tradition teaches the educational values of maintaining water quality, sustainable water management, and environmental awareness to the younger generation. Ngalun Aik also strengthens cultural ties, spirituality, and ecological awareness in the community.